Self-protection super-hydrophobic antibacterial nano titanium dioxide tube / PTFE (polytetrafluoroethylene) composite material as well as preparation method and activation method thereof

By introducing modified nanotitanium dioxide tubes into superhydrophobic polytetrafluoroethylene materials and using laser activation to form micro-nano composite structures, the problem of easy damage in actual applications is solved, and the self-protective superhydrophobic and antibacterial properties are improved.

CN119875272APending Publication Date: 2025-04-25HEFEI INNOVATION RES INST BEIHANG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510183965.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing superhydrophobic polytetrafluoroethylene materials are easily worn and damaged in actual applications, resulting in surface failure, and laser processing technology has problems of high energy consumption and low efficiency.

Method used

Modified nanotitanium dioxide tubes are combined with polytetrafluoroethylene, and activated by laser one-time scanning to form a micro-nano composite structure across scales, thereby achieving the optimal superhydrophobic effect, and the photocatalytic action of nanotitanium dioxide tubes is used to achieve antibacterial effects.

Benefits of technology

The self-protective superhydrophobic and antibacterial properties of the material surface are realized, avoiding the loss of function during transportation and processing, and improving the weather resistance and catalytic sterilization function of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875272A_ABST
    Figure CN119875272A_ABST
Patent Text Reader

Abstract

The invention relates to a self-protection super-hydrophobic antibacterial nano titanium dioxide tube / PTFE (polytetrafluoroethylene) composite material as well as a preparation method and a laser activation method thereof. The self-protection super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material is prepared from polytetrafluoroethylene, a modified nano titanium dioxide tube, acrylic resin, an antioxidant, a dispersing agent and a silane coupling agent according to the mass ratio of (60-100): (15-30): (0.5-3): (0.2-3): (0.2-3): (1-5). By introducing the modified nano titanium dioxide tube, the obtained self-protection super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material is activated by laser, polytetrafluoroethylene on the surface layer of the material is gasified and removed, and the nano titanium dioxide tube is exposed, so that a cross-scale micro-nano composite structure is formed through activation; therefore, the optimal super-hydrophobic effect is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of super-hydrophobic materials, and in particular to a self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material and a preparation method and an activation method thereof. Background Art

[0002] Polytetrafluoroethylene is a special polymer material with excellent performance, which has excellent properties such as corrosion resistance, high sealing, high and low temperature resistance, self-lubrication, and electrical insulation. Since the molecular chain does not contain hydrophilic groups such as -OH and -COOH, the surface energy of polytetrafluoroethylene materials is extremely low. Under unmodified conditions, polytetrafluoroethylene materials have a certain degree of hydrophobicity. Therefore, polytetrafluoroethylene is an ideal material for preparing super-hydrophobic films, and has broad application prospects in various fields such as military industry, aerospace, new energy, and transportation.

[0003] Generally, the methods for preparing super-hydrophobic materials can be divided into two categories: surface chemical modification and preparation of surface microstructures. Chemical modification is the chemical treatment of the material surface to further reduce the surface energy of the material. However, due to the extremely low surface energy of polytetrafluoroethylene itself, chemical modification has limited room for improving the hydrophobic properties of polytetrafluoroethylene. There are many methods for preparing surface microstructures, including template method, phase separation, etching method, shower / spraying method, electrospark micromachining, electroplating method, sol-gel method, etc. These methods have their own advantages, but are subject to problems such as preparation mechanism, cost, efficiency, product wear resistance, and hydrophobic life; at the same time, the material surfaces with super-hydrophobic properties obtained by these methods are easily damaged by wear during practical applications (such as transportation, cutting, pasting, molding, installation, etc.), resulting in surface failure.

[0004] In recent years, due to the characteristics of high brightness, high directivity, high monochromaticity and high coherence of lasers, the use of laser processing technology to prepare super-hydrophobic surfaces of polytetrafluoroethylene materials has attracted more and more attention. For example, the patent with publication number CN104494134B discloses a method for preparing super-hydrophobic polytetrafluoroethylene surfaces using CO2 lasers. This method is based on the ablation mechanism of high-power CO2 laser processing. Toxic and harmful gases such as hydrogen fluoride and CO are inevitably produced during the processing, and the energy consumption is high and the efficiency is low. For example, the patent with publication number CN112605531A discloses a method for directly preparing super-hydrophobic surfaces on polytetrafluoroethylene materials using femtosecond lasers. This method uses the characteristics of "cold processing" of femtosecond lasers to effectively avoid the generation of toxic and harmful gases; however, this method requires multiple scans of the laser to prepare characteristic structures, which is inefficient and cannot meet the needs of actual large-format scenes. Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material and a preparation method and an activation method thereof. The self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material introduces a modified nano-titanium dioxide tube, and a cross-scale micro-nano composite structure can be obtained by a one-time laser scanning activation, thereby obtaining the optimal super-hydrophobic effect.

[0006] To achieve the above object, the present invention adopts the following technical solutions: The invention firstly provides a self-protection super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material, which is prepared from polytetrafluoroethylene, modified nano titanium dioxide tube, acrylic resin, antioxidant, dispersant and silane coupling agent in a mass ratio of 60-100:15-30:0.5-3:0.2-3:0.2-3:1-5.

[0007] As a further improvement of the above scheme of the present invention, the preparation method of the modified nano titanium dioxide tube comprises the following steps: polishing and laser roughening the metal titanium substrate in sequence to obtain a treated metal titanium substrate; using the treated metal titanium substrate as an anode for electrochemical reaction to obtain a suspension solution containing nano titanium dioxide tubes, and post-processing to obtain modified nano titanium dioxide tubes.

[0008] As a further improvement of the above solution of the present invention, the metal titanium substrate is a sheet structure, and the polishing is to polish the metal titanium substrate with sandpaper, and the sandpaper is selected from at least one of 500-5000 mesh sandpaper; And / or, the laser used for the laser texturing is one of nanosecond pulse laser, picosecond pulse laser and femtosecond pulse laser; And / or, the average power of the laser for laser texturing is 200-1000W, the spot diameter is 20-100μm, the laser frequency is 50-200KHz, the wavelength is 800-1100nm, the filling line spacing is 10-120μm, the scanning rate is 100-3000mm / s, the defocus amount is 0, the number of scans is 1, and the laser filling method is at least one of grid filling, parallel line filling, and cross filling.

[0009] As a further improvement of the above scheme of the present invention, the cathode of the electrochemical reaction is a platinum sheet, and the electrolyte is an ethylene glycol solution containing ammonium fluoride and deionized water. In the ethylene glycol solution, the concentration of ammonium fluoride is 1wt%-1.2wt%, and the concentration of deionized water is 5vol%-7.5vol%; And / or, the electrochemical reaction is performed twice, the first electrochemical reaction time is 0.5-0.75h. The second electrochemical reaction time is 1.5-1.75h, and the voltage of the electrochemical reaction is constant at 80-110V. Preferably, after the first electrochemical reaction and before the second electrochemical reaction, the metal titanium substrate is taken out and laser cleaned, and the surface of the metal titanium substrate is treated to remove the oxide film.

[0010] As a further improvement of the above scheme of the present invention, the post-treatment is to filter the suspension solution, and wash and dry the solid matter with alcohol; the alcohol washing is to use ethanol, n-butanol or ethylene glycol to clean the solid matter, and the drying is to dry in a vacuum environment at 60-90°C.

[0011] As a further improvement of the above scheme of the present invention, the antioxidant is at least one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxyphenyl)benzene.

[0012] And / or, the dispersant is at least one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant; preferably, the dispersant is at least one of cetylpyridinium chloride, cetyldimethylbenzylammonium chloride, cetyltrimethyl, cetyltrimethylammonium bromide, alkylbenzene sulfonate, sodium benzyl sulfonate, sodium medium alkyl sulfate, polyethylene glycol distearate, fatty alcohol polyoxyethylene ether, and hydroxyethyl cellulose ether.

[0013] And / or, the silane coupling agent is one of KH540, KH550, KH560, and KH602.

[0014] The present invention also proposes a method for preparing the self-protective super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material as described above, which comprises the following steps: uniformly mixing polytetrafluoroethylene, modified nano-titanium dioxide tube, acrylic resin, antioxidant, dispersant and silane coupling agent in proportion to obtain a mixture; extruding and granulating the mixture through a screw extruder, and then processing it into a predetermined shape to obtain a self-protective super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material.

[0015] As a further improvement of the above scheme of the present invention, the screw extruder is arranged in six temperature zones from the hopper to the die head, wherein the temperature of zone one is 200-220°C, the temperature of zone two is 360-380°C, the temperature of zone four is 360-380°C, the temperature of zone five is 360-380°C, the temperature of the die head is 350-370°C, and the screw speed is 200-280r / min.

[0016] The present invention also proposes a laser activation method for the self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material as described above, which comprises the following steps: wiping the surface of the self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material, performing laser scanning on the surface of the self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material to form a micron-level characteristic structure, and cleaning to obtain a super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material.

[0017] As a further improvement of the above scheme of the present invention, the average laser power of the laser scanning is 5-20W, the spot diameter is 20-100μm, the laser frequency is 50-200KHz, the pulse width is 100-1000fs, the wavelength is 800-1100nm, the filling line spacing is 10-120μm, the scanning rate is 100-3000mm / s, the defocus amount is 0, the number of scans is 1, and the laser filling method is at least one of grid filling, parallel line filling, and cross filling; And / or, the micrometer-scale characteristic structure is one of a groove structure, a cone structure, and a cone array structure.

[0018] As a further improvement of the above scheme of the present invention, the wiping is performed by using an organic solvent, and the organic solvent is ethanol, n-butanol or ethylene glycol; and the cleaning is performed by air blowing.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention introduces modified nano titanium dioxide tubes, and activates the obtained self-protective super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material through laser. The polytetrafluoroethylene on the surface of the material is gasified and removed, and the nano titanium dioxide tube is exposed, thereby activating to form a cross-scale micro-nano composite structure, so as to obtain the best super-hydrophobic effect; and the modified nano titanium dioxide tubes are introduced, and the photocatalytic effect of titanium dioxide under sunlight, especially ultraviolet irradiation, is utilized to generate highly active OH-, OOH- and other free radicals on the surface to play a bactericidal and antibacterial role, and the nano titanium dioxide tube has a higher specific surface area, so that the nano titanium dioxide tube / PTFE composite material has a better catalytic bactericidal function; further, the introduced modified nano titanium dioxide tube can also toughen the polytetrafluoroethylene-based material, effectively improving the weather resistance of the super-hydrophobic performance of the product.

[0020] 2. After the self-protection super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material of the present invention is manufactured, the material is in a self-protection state and is laser activated after reaching the use state, which can effectively prevent the functional surface of the material from being damaged during the transportation, cutting, pasting, installation and other processes, causing loss of function.

[0021] 3. The present invention introduces acrylic resin into the material, which can improve the adhesion between the nano titanium dioxide tube and the polytetrafluoroethylene base material, improve the leveling property of the material, and is beneficial to the preparation of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the laser activation principle of the self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material of the present invention; Figure 2 The surface microstructure of the super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample obtained in Example 1; Figure 3 This is a contact angle test photograph of the super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample obtained in Example 1. DETAILED DESCRIPTION

[0023] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0025] The raw materials used in the following examples are as follows: Polytetrafluoroethylene (850A), DuPont; Evonik; acrylic resin (JONCRYL ECO 684), BASF; antioxidants (Irganox1010, Irganox168, Irganox1330), Ciba Specialty Chemicals, Switzerland; silane coupling agent (KH550), Dow Corning.

[0026] Example 1 This embodiment provides a self-protective super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material, which is prepared from polytetrafluoroethylene, modified nano-titanium dioxide tube, acrylic resin, antioxidant, dispersant, and silane coupling agent in a mass ratio of 80:15:1:0.5:1:3.

[0027] The preparation method of the self-protection super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material of this embodiment comprises the following steps S11-S16: S11. The titanium sheet is polished with 1000-grit sandpaper, and then roughened with nanosecond laser to obtain a roughened titanium sheet, wherein the average power of the nanosecond laser is 500w, the spot diameter is 30μm, the laser frequency is 100kHz, the wavelength is 800nm, the filling line spacing is 30μm, the scanning rate is 1000mm / s, the defocus amount is 0, the number of scans is 1, and the laser filling method is grid filling.

[0028] S12. The roughened titanium sheet obtained in step S11 is placed in an ethylene glycol solution (in the ethylene glycol solution, the ammonium fluoride concentration is 1wt% and the deionized water concentration is 5 vol%), and subjected to a two-step oxidation treatment under a constant voltage of 80V. The first oxidation reaction time is 0.5h. After the first oxidation reaction, the surface of the titanium sheet is treated to remove the oxide film by laser cleaning, and then a second oxidation reaction is carried out. The second oxidation reaction time is 1.5h to obtain a suspension solution containing nano-titanium dioxide tubes.

[0029] S13. Filter the suspension solution containing nano-titanium dioxide tubes, wash the product with ethanol, and then place the product in a vacuum drying oven at 70° C. to obtain modified nano-titanium dioxide tubes.

[0030] S14. Weigh polytetrafluoroethylene, modified nano-titanium dioxide tubes, acrylic resin, antioxidant, dispersant and silane coupling agent in proportion and stir and mix well to obtain a mixture; S15. The mixed material obtained in step S14 is extruded and granulated through a twin-screw extruder, wherein the temperature distribution of the twin-screw extruder is as follows: zone 1 temperature 200°C, zone 2 temperature 360°C, zone 4 temperature 360°C, zone 5 temperature 360°C, die head temperature 350°C, and screw speed 220r / min.

[0031] S16. Extrude and calender the material obtained in step S15 to obtain a self-protected super-hydrophobic and antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene composite sheet.

[0032] Combination Figure 1 After the self-protective super-hydrophobic antibacterial modified nano titanium dioxide tube / polytetrafluoroethylene composite sheet prepared in this embodiment reaches the use conditions, laser activation treatment is performed according to the following steps S21-S22: S21. Wipe and clean the surface of the self-protecting super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene composite sheet with ethanol; perform laser activation on the surface of the sheet: The laser focus was adjusted according to the position of the sheet and the processing area was set. The initial process parameters of the femtosecond laser were as follows: the average laser power was 10W, the spot diameter was 20μm, the laser frequency was 50KHz, the pulse width was 350fs, the wavelength was 800nm, the filling line spacing was 30μm, the scanning rate was 1000mm / s, the defocus amount was 0, the number of scans was 1, and the laser filling method was grid filling; a cross-scale micro-nano composite structure combining micron-scale grooves and nano-scale tubular protrusions was formed on the surface of the sheet; S22. Blow air through the laser-activated sheet to remove dust on the surface of the sheet and fine particles splashed out by laser processing, and obtain a super-hydrophobic and antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample.

[0033] Figure 2 and Figure 3 The following are the surface microstructure diagram and contact angle test photos of the super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample obtained in this embodiment. According to the test, the contact angle of the water drop on the surface of the super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample obtained in this embodiment reached 164.7°, and the antibacterial rate against Staphylococcus aureus and Escherichia coli reached 96%. It can be seen that the super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample obtained in this embodiment exhibits excellent super-hydrophobic and antibacterial properties.

[0034] Example 2 This embodiment provides a self-protective super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material, which is prepared from polytetrafluoroethylene, modified nano-titanium dioxide tube, acrylic resin, antioxidant, dispersant, and silane coupling agent in a mass ratio of 100:30:3:2:2:3.

[0035] The preparation method of the self-protection super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material of this embodiment comprises the following steps S11-S16: S11. The titanium sheet was polished with 3000-grit sandpaper, and then roughened with nanosecond laser to obtain a roughened titanium sheet, wherein the average power of the nanosecond laser was 1000w, the spot diameter was 80μm, the laser frequency was 100kHz, the wavelength was 1030nm, the filling line spacing was 50μm, the scanning rate was 15000mm / s, the defocus was 0, the number of scans was 1, and the laser filling method was grid filling.

[0036] S12. The roughened titanium sheet obtained in step S11 is placed in an ethylene glycol solution (in the ethylene glycol solution, the ammonium fluoride concentration is 1.2wt% and the deionized water concentration is 7.5 vol%), and subjected to a two-step oxidation treatment under a constant voltage of 110V. The first oxidation reaction time is 0.75h. After the first oxidation reaction, the surface of the titanium sheet is treated to remove the oxide film by laser cleaning, and then a second oxidation reaction is carried out. The second oxidation reaction time is 1.75h to obtain a suspension solution containing nano-titanium dioxide tubes.

[0037] S13. Filter the suspension solution containing nano-titanium dioxide tubes, wash the product with ethanol, and then place the product in a vacuum drying oven at 70° C. to obtain modified nano-titanium dioxide tubes.

[0038] S14. Weigh polytetrafluoroethylene, modified nano-titanium dioxide tubes, acrylic resin, antioxidant, dispersant and silane coupling agent in proportion and stir and mix well to obtain a mixture; S15. The mixed material obtained in step S14 is extruded and granulated through a twin-screw extruder, wherein the temperature distribution of the twin-screw extruder is as follows: zone 1 temperature 220°C, zone 2 temperature 380°C, zone 4 temperature 380°C, zone 5 temperature 380°C, die head temperature 360°C, and screw speed 260r / min.

[0039] S16. Extrude and calender the material obtained in step S15 to obtain a self-protected super-hydrophobic and antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene composite sheet.

[0040] Combination Figure 1 After the self-protective super-hydrophobic antibacterial modified nano titanium dioxide tube / polytetrafluoroethylene composite sheet prepared in this embodiment reaches the use conditions, laser activation treatment is performed according to the following steps S21-S22: S21. Wipe and clean the surface of the self-protecting super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene composite sheet with ethanol; perform laser activation on the surface of the sheet: The laser focus was adjusted according to the position of the sheet and the processing area was set. The initial process parameters of the femtosecond laser were as follows: the average laser power was 20 W, the spot diameter was 50 μm, the laser frequency was 200 KHz, the pulse width was 700 fs, the wavelength was 1000 nm, the filling line spacing was 100 μm, the scanning rate was 2500 mm / s, the defocus amount was 0, the number of scans was 1, and the laser filling method was cross-filling; a cross-scale micro-nano composite structure combining a micron-scale conical array and nano-scale tubular protrusions was formed on the surface of the sheet; S22. Blow air through the laser-activated sheet to remove dust on the surface of the sheet and fine particles splashed out by laser processing, and obtain a super-hydrophobic and antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample.

[0041] After testing, the contact angle of water droplets on the surface of the super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample obtained in this embodiment reached 158.6°, and the antibacterial rate against Staphylococcus aureus and Escherichia coli reached 93%. It can be seen that the super-hydrophobic antibacterial modified nano-titanium dioxide tube / polytetrafluoroethylene sample obtained in this embodiment exhibits excellent super-hydrophobic and antibacterial properties.

[0042] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0043] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material, characterized in that: The invention is prepared from polytetrafluoroethylene, modified nano titanium dioxide tube, acrylic resin, antioxidant, dispersant and silane coupling agent in a mass ratio of 60-100:15-30:0.5-3:0.2-3:0.2-3:1-5.

2. The self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material according to claim 1, characterized in that: The preparation method of the modified nano titanium dioxide tube comprises the following steps: grinding and laser roughening a metal titanium substrate in sequence to obtain a treated metal titanium substrate; using the treated metal titanium substrate as an anode for electrochemical reaction to obtain a suspension solution containing nano titanium dioxide tubes, and post-processing to obtain the modified nano titanium dioxide tubes.

3. The self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material according to claim 2, characterized in that: The metal titanium substrate is a sheet structure, and the polishing is performed by using sandpaper to polish the metal titanium substrate, and the sandpaper is selected from at least one of 500-5000 mesh sandpaper; And / or, the laser used for the laser texturing is one of nanosecond pulse laser, picosecond pulse laser and femtosecond pulse laser; And / or, the average power of the laser for laser texturing is 200-1000W, the spot diameter is 20-100μm, the laser frequency is 50-200KHz, the wavelength is 800-1100nm, the filling line spacing is 10-120μm, the scanning rate is 100-3000mm / s, the defocus amount is 0, the number of scans is 1, and the laser filling method is at least one of grid filling, parallel line filling, and cross filling.

4. The self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material according to claim 2, characterized in that: The cathode of the electrochemical reaction is a platinum sheet, and the electrolyte is an ethylene glycol solution containing ammonium fluoride and deionized water. In the ethylene glycol solution, the concentration of ammonium fluoride is 1wt%-1.2wt%, and the concentration of deionized water is 5vol%-7.5vol%; And / or, the electrochemical reaction is performed twice, the first electrochemical reaction time is 0.5-0.75h, the second electrochemical reaction time is 1.5-1.75h, and the voltage of the electrochemical reaction is constant at 80-110V.

5. The self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material according to claim 2, characterized in that: The post-treatment is to filter the suspension solution, wash the solid with alcohol and dry it; the alcohol washing is to use ethanol, n-butanol or ethylene glycol to clean the solid, and the drying is to dry it in a vacuum environment at 60-90°C.

6. The self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material according to claim 1, characterized in that: The antioxidant is at least one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxyphenyl)benzene; And / or, the dispersant is at least one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant; And / or, the silane coupling agent is one of KH540, KH550, KH560, and KH602.

7. A method for preparing a self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material as described in any one of claims 1 to 6, characterized in that: It includes the following steps: Polytetrafluoroethylene, modified nano titanium dioxide tube, acrylic resin, antioxidant, dispersant and silane coupling agent are uniformly mixed in proportion to obtain a mixture; the mixture is extruded and granulated by a screw extruder, and then processed into a predetermined shape to obtain a self-protective super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material.

8. The method for preparing a self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material according to claim 7, characterized in that: The screw extruder has six temperature zones arranged in sequence from the hopper to the die head, wherein the temperature of zone one is 200-220°C, the temperature of zone two is 360-380°C, the temperature of zone four is 360-380°C, the temperature of zone five is 360-380°C, the temperature of the die head is 350-370°C, and the screw speed is 200-280r / min.

9. A laser activation method for a self-protected super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material as claimed in any one of claims 1 to 8, characterized in that: It includes the following steps: The surface of the self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material is wiped, and laser scanning is performed on the surface of the self-protecting super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material to form a micron-level characteristic structure, and the surface is cleaned to obtain a super-hydrophobic antibacterial nano-titanium dioxide tube / PTFE composite material.

10. The laser activation method of the self-protecting super-hydrophobic antibacterial nano titanium dioxide tube / PTFE composite material according to claim 9, characterized in that: The laser scanning has an average laser power of 5-20W, a spot diameter of 20-100μm, a laser frequency of 50-200KHz, a pulse width of 100-1000fs, a wavelength of 800-1100nm, a filling line spacing of 10-120μm, a scanning rate of 100-3000mm / s, a defocus amount of 0, a scanning number of 1 times, and a laser filling mode of at least one of grid filling, parallel line filling, and cross filling; And / or, the micrometer-scale characteristic structure is one of a groove structure, a cone structure, and a cone array structure; And / or, the wiping is performed using an organic solvent, the organic solvent is ethanol, n-butanol or ethylene glycol; and the cleaning is performed by air blowing.

Citation Information

Patent Citations

  • Method for preparing superhydrophobic surface material with adjustable contact angle by one-step laser method

    CN104494134B

  • Method for preparing structure and wettability adjustable anti-icing polytetrafluoroethylene super-hydrophobic surface by femtosecond laser

    CN112605531A